Lao People's Democratic Republic : First Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Lao People's Democratic Republic's First Review Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criteria. Performance in the first year of the PRGF arrangement has been generally satisfactory. Fiscal slippages through September 2001, owing to weaknesses in the early implementation of the decentralization initiative, were corrected in the December quarter, thus bringing the fiscal program back on track. For 2001/02, the program aims at GDP growth of at least 5 percent, and inflation at about 6 percent by year-end.